Two new species of the genus Monstrillopsis Sars, 1921 (Copepoda: Monstrilloida: Monstrillidae) from South Korea - Lee, Jimin; Kim, Dongsung; Chang, Cheon Young (Zootaxa, 2016)
Monstrilloid copepods of the genus Monstrillopsis Sars, 1921 are recorded from Korea, as well as from the northwestern Pacific, for the first time. Specimens were obtained using a light trap set overnight at piers or seawalls in small harbors. Males of two new species were found and are described herein with remarks on their affinities and detailed drawings and SEM photographs of their morphological features. Monstrillopsis longilobata sp. nov. is allied to M. chathamensis Suárez-Morales & Morales-Ramírez, 2009 and M. sarsi Isaac, 1974 in having the character combination of a long, claw-like apical spinous process on the male antennule and elongate genital lappets. It differs from them in having conspicuous transverse striations on the dorsal surface of the cephalothorax and extremely long male genital lappets, which extend far beyond the anterior margins of the caudal rami. Monstrillopsis coreensis sp. nov. also has a claw-like apical spinous process of the male antennule and conspicuous transverse striations on the dorsal surface of the cephalothorax, but it differs from M. longilobata in having a much longer and stronger apical spine of the antennule and a relatively shorter and undulating genital apparatus.